3x = -39

3x = -39; x = -39/3; x = -13

Question

Asked 1/4/2016 9:07:46 AM

Updated 1/4/2016 9:24:30 AM

1 Answer/Comment

Rating

3

3x = -39;

x = -39/3;

x = -13

x = -39/3;

x = -13

Added 1/4/2016 9:24:30 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [1/4/2016 9:33:13 AM]

Solve for x.
9x - 1 = -11 **Weegy:** A.x= -1.1/9 (More)

Question

Expert Answered

Updated 1/4/2016 9:27:13 AM

1 Answer/Comment

Which of the following represents "four times the square of a number is thirty-six"? **Weegy:** 4x^2 = 36 represents "four times the square of a number is thirty-six". **User:**
If a hypothesis is supported by several experiments, it may become a(n) _____.
law
theory
fact
educated guess (More)

Question

Not Answered

Updated 1/9/2016 7:11:25 AM

1 Answer/Comment

8(x + 1) - 3(x + 4) = 7(2 - x)

Question

Expert Answered

Updated 1/5/2016 7:59:23 AM

1 Answer/Comment

8(x + 1) - 3(x + 4) = 7(2 - x)

5x - 4 = -7x + 14

5x - 4 = -7x + 14 + 7x

12x - 4 = 14

12x = 14 + 4

12x = 18

x = 18/12

x = 3/2

5x - 4 = -7x + 14

5x - 4 = -7x + 14 + 7x

12x - 4 = 14

12x = 14 + 4

12x = 18

x = 18/12

x = 3/2

Added 1/5/2016 7:59:23 AM

This answer has been confirmed as correct and helpful.

A literal equation has only one variable **Weegy:** A literal equation has only one variable. FALSE. (More)

Question

Expert Answered

Updated 1/5/2016 8:07:18 AM

0 Answers/Comments

27,694,301

questions answered

There are no comments.